The extent to which commercial banks rely on financial analysis in making financial and credit decisions (An applied study on a sample of commercial banks in the city of Sebha) (Economic studies journal, 2024)
The study aimed to identify the extent to which commercial banks rely on financial analysis to rationalize financial and financing decision-making. In order to achieve the objectives of the study, it relied on the descriptive analytical approach for a sample of 41 employees in credit departments in commercial banks operating in the city of Sebha, the sample of the study, and data was collected. The primary data collection tool was a questionnaire, which was analyzed using SPSS. The most important results were that the banks in the study sample considered the guarantees provided by the financing applicant to be among the most important basics of granting financing, as well as the client’s personality and reputation. In general, banks rely on financial analysis in the financial and financing decision-making process. The study recommended the need to increase attention to relying on financial analysis as a basis for making financial and credit decisions.
Keywords: financialanalysis; ecisionmaking; commercial banks